Concepts of South-South Economic Cooperation - A. V. Kuznetsov (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2019)
The paper traces the evolution of conceptual approaches to South-South economic cooperation. It is shown that with the collapse of the bipolar system and the rise of globalization the interest in South-South cooperation have risen again, and compared to the 1950–1970-ies focuses more on economic relations of developing countries. At the same time, the article shows that the deepening differentiation of the countries of the global South allows us to consider the South-South dialogue as ambiguous process. According to the author, this is a set of relations of very different level of interaction between developing countries, which are part of a more fundamental process of transformation of the existing “Westcentric” world order. The paper identifies four such levels, characterized by very different opportunities for participating in economic ties between developing countries: relations of major countries of the South with each other (especially in BRICS and IBSA groups); the interaction of the largest countries with other developing countries (most known for the cooperation in the framework of “One belt, one road” Chinese initiative); intensive contacts of countries of the global South due to the objectively existing neighborhood effect (the most famous integration groupings are ASEAN in Southeast Asia and MERCOSUR in Latin America); and cross-border ties of small developing countries geographically distant from each other. The paper concludes that South-South cooperation cannot be a full-fledged alternative to other global economic ties. Indeed, countries of the global North dominate in many areas and more often still offer mutually beneficial cooperation to developing countries, so that isolation from the global North is akin to autarky. South-South cooperation should be viewed primarily as a way to develop additional forms of interaction different from that dominant in the contemporary world, prescribed mainly taking into account the views of several leading economic powers. Thus, it is correct to speak of South- non-West cooperation, referring to rather developed countries that are not able to build relations with the US and key EU countries (e.g. Russia).